2008
DOI: 10.1111/j.1461-0248.2008.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

15N enrichment as an integrator of the effects of C and N on microbial metabolism and ecosystem function

Abstract: Organic carbon (C) and nitrogen (N) are essential for heterotrophic soil microorganisms, and their bioavailability strongly influences ecosystem C and N cycling. We show here that the natural (15)N abundance of the soil microbial biomass is affected by both the availability of C and N and ecosystem N processing. Microbial (15)N enrichment correlated negatively with the C : N ratio of the soil soluble fraction and positively with net N mineralization for ecosystems spanning semiarid, temperate and tropical clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 56 publications
(119 reference statements)
7
126
2
Order By: Relevance
“…This was further supported by low C/N and increasing enrichment of 15 N in DOM. The latter indicates a repeated microbial recycling of N in DOM, which would be in line with a strong N deficiency at the sites and an enrichment of 15 N due to higher humification (Dijkstra et al, 2008). In contrast, Kalbitz and Geyer (2002) found low δ 15 N values in highly humified DOM, but this may be explained by a varying contribution of DON supply from either the solid phase or organic matter mineralization.…”
Section: Decomposition Versus Doc Concentrations and Dom Isotopic Sigmentioning
confidence: 60%
“…This was further supported by low C/N and increasing enrichment of 15 N in DOM. The latter indicates a repeated microbial recycling of N in DOM, which would be in line with a strong N deficiency at the sites and an enrichment of 15 N due to higher humification (Dijkstra et al, 2008). In contrast, Kalbitz and Geyer (2002) found low δ 15 N values in highly humified DOM, but this may be explained by a varying contribution of DON supply from either the solid phase or organic matter mineralization.…”
Section: Decomposition Versus Doc Concentrations and Dom Isotopic Sigmentioning
confidence: 60%
“…with 0-4% lower d 15 N than the bulk original organic matter (Lehmann et al 2002;Dijkstra et al 2008; C. Yoshimizu, unpublished data).…”
Section: Turnover Of Nomentioning
confidence: 96%
“…As a consequence, D 15 N SMB/WSN increased significantly with time. It has been suggested that the relationship between the the 15 N enrichment of the microbial biomass relative to that of the water soluble fraction and C/N ratio of the water soluble fraction is an indicator of change in microbial N metabolism (Dijkstra et al 2008). Here, a significant linear regression (r 2 = 0.66, P \ 0.001, y = 3.35 -1.17x) was also found between C/N ratio of the water soluble fraction and D 15 N SMB/WSN .…”
Section: Changes In D 13 C and D 15 N Valuesmentioning
confidence: 99%